PENGEMBANGAN MEDIA BERBASIS FLASH PELAJARAN IPA (GAYA) PADA SISWA KELAS VIII - Zahroh, Dian Dwiyanti; Efendi, Mohammad; Wahyuno, Endro (Jurnal Ortopedagogia, 2015)
Abstract : A hearing impairmentÂ is someone suffering limitation of hearing. The limitation make student with hearing impairment have some problem with comunication. Limitation of comunication make students with heraing impairment need instuctionalÂ media when studying in class. Natural science is one of the lessons that are verbal. The media is really needed to teach students with hearing imparment. The purpose of the study is developing natural science product of gaya material based on the flash style.this studyÂ used the method developed by Lee & Owens. The concluded of the reseacrh showed that the instructional media can be used in learning activity with show validKey Word: Visual Media, Hearing impairmentAbstrak :Tunarungu adalah seseorang yang mengalami keterbatasan dalam pendengarannya. Keterbatasan tersebut membuat siswa tunarungu mengalami hambatan dalam berkomunikasi, sehingga siswa tunarungu membutuhkan media dalam proses pembelajaran. IPA adalah salah satu pelajaran yang bersifat verbal. Pelajaran IPA khususnya materi gaya untuk anak tunarungu sangat membutuhkan media. Penelitian ini bertujuan menghasilkan produk IPA materi gaya berbasis flash. Penelitian ini menggunakan metode yang dikembangkan oleh Lee & Owens. Penelitian ini menunjukkan bahwa media berbasis flah dapat digunakan dalam pembelajaran dengan bukti yang valid.